论致良知的公共伦理意涵 = Analysis of the value of Zhi Liang Zhi as public ethics - 吴建璋 Oh, Jian Zhang (2016)
王守仁（1472年-1529年），字伯安，号阳明子，人称王阳明，是明中叶的心学大儒。阳明于正德十六年(1521年)，五十岁时，提出了“致良知”说。在这之前，宋代至明初期深受程朱理学的影响。理学以“存理灭欲”和“即物穷理”为重，最终不免形成社会和学习氛围的高压性的流弊。究其原因，就是以天理为客观之理，以道德为外铄，或“义外”的流弊。致良知的提出，指出了人们固有道德至善的潜能，无需靠外援，是对“义外”的革新。致良知就是将这份固有的道德推至天下，达到普遍有效性。王阳明提出此说后，时人学者对他的褒贬不一，有人称他为丧心病狂之徒，也有人深信不疑。不仅当时的学者认为致良知有务内遗外之弊，现今的学者也质疑致良知并不具备一种公共的本质。对此，论文将扣紧明中叶的历史脉络，剖析阳明的思想与世界观；并进一歩从“公共伦理”角度，探究致良知的公共意涵。Wang Shouren (1472-1529), more commonly known as Wang Yangming, is an established Neo-Confucian Scholar during the Ming Dynasty. He developed his Zhi Liang Zhi （致良知）approach during his late years in 1521. Prior to this, from the previous Song Dynasty to the early stages of Ming Dynasty, the society was heavily influenced by the Chengzhu school of thought (程朱理学) which proposes that tianli （天理）is something that is out there in the world for people to know, to acquire and that one must strive to understand tianli and eliminate the renyu （人欲）which is innate in one’s consciousness. However, when Wang proposed Zhi Liang Zhi in the mid-Ming era, it was a revolutionary thought which suggests that tianli is innate in one’s consciousness just as renyu and that one can eventually extend this innate tianli to the rest of the world, or in a modern sense formulating public ethics. This led many to doubt his thought as crazy, even criticising it as too focused on internal enlightenment and ignoring the reality, or in the modern sense, not worthy of public ethics. As such, my report will be focused on understanding Wang’s Zhi Liang Zhi approach from its historical context and then using the rules of public ethics namely total equality, proportional equality to conclude if Zhi Liang Zhi is of worth to public ethics.